The Alysiinae (Hym., Braconidae) parasites of the Agromyzidae (Diptera). I. General questions of taxonomy, biology and evolution. - Griffiths, Graham C. D. (Contributions to Entomology = Beiträge zur Entomologie, 1964)
1. This paper is intended to be the first of a series dealing with the Alysiinae parasites of the Agromyzidae. The majority of these belong to the Dacnusini, and it is with that tribe that this paper is principally concerned. - 2. The morphological characters of the Alysiinae are analysed according to the principles of phylogenetic systematics defined by Hennig (1950) and as a result of this analysis a phylogeny tree is produced and changes are proposed in the previously accepted classification. The significance of the exodont mandibles of the Alysiinae is discussed and it is concluded that their normal function is to help secure the parasite’s escape from puparia of cyclorrhaphous Diptera. - 3. Most Dacnusini show an exceptionally high degree of host specificity. Comparison of their phylogeny with their host association leads to the conclusion that the common ancest or of the tribe was probably associated with the ancestor(s) of one or both of two groups of Agromyzidae which are leaf-miners of monocotyledons. These are the Agromyza nigripes ambigua group and Cerodontha s. l. - 4. Appendices given include a practical key to the genera of Dacnusini, notes on some of Thomsons’s (1895) and Förster’s (1862) types, a revision of the Chorebus nydia group and descriptions of the new genus Protodacnusa and its species. One new species is described in the Chorebus nydia group and two in Protodacnusa. Nomenclatural Acts miser Nixon, 1954 (Antrusa), syn. n. of Protodacnusa aridula (Thomson, 1895) persimilis Nixon, 1954 (Antrusa), syn. n. of Exotela melanocera (Thomson, 1895) Ametria Förster, 1862 (Braconidae), syn. n. of Chorebus Haliday, 1833 Chorebidea Nixon, 1943 (Braconidae), syn. n. of Chaenusa Haliday, 1839 Chorebidella Riegel, 1950 (Braconidae), syn. n. of Chaenusa Haliday, 1839 Coelinidea Viereck, 1913 (Braconidae), syn. n. of Coelinius Nees, 1818 Ectilis Nixon, 1943 (Braconidae), syn. n. of Synelix Förster, 1862 Eriocoelinius Viereck, 1913 (Braconidae), syn. n. of Coelinius Nees, 1818 Etriptes Nixon, 1943 (Braconidae), syn. n. of Chorebus Haliday, 1833 Gyrocampa Förster, 1862 (Braconidae), syn. n. of Chorebus Haliday, 1833 Paragyrocampa Tobias, 1962 (Braconidae), syn. n. of Chorebus Haliday, 1833 Phaenolexis Förster, 1862 (Braconidae), syn. n. of Chorebus Haliday, 1833 Polemochartus Schulz, 1911 (Braconidae), syn. n. of Coelinius Nees, 1818 Polemon Giraud, 1863 (Braconidae), syn. n. of Coelinius Nees, 1818 Protodacnusa Griffiths, 1964 (Braconidae), gen. n. Sarops Nixon, 1942 (Braconidae), syn. n. of Synelix Förster, 1862 Stiphrocera Förster, 1862 (Braconidae), syn. n. of Chorebus Haliday, 1833 ampliator (Nees, 1834) (Chorebus), comb. n. hitherto Alysia ampliator brevicornis (Thomson, 1895) (Chorebus), comb. n. hitherto Alysia (Dacnusa) brevicornis cinctus (Haliday, 1839) (Chorebus), Lectotype; comb. n. hitherto Alysia (Dacnus) cincta coxator (Thomson, 1895) (Chorebus), Lectotype; comb. n. hitherto Dacnusa (Dacnusa) coxator crenulatus (Thomson, 1895) (Chorebus), comb. n. hitherto Dacnusa (Dacnusa) crenulata glabriculus (Thomson, 1895) (Chorebus), comb. n. hitherto Dacnusa (Dacnusa) glabricula lateralis (Haliday, 1839) (Chorebus), comb. n. hitherto Alysia (Dacnusa) lateralis nydia (Nixon, 1937) (Chorebus), comb. n. hitherto Dacnusa nydia spenceri Griffiths, 1964 (Chorebus), spec. n. bellina Nixon, 1937 (Dacnusa), syn. n. of Exotela cyclogaster Förster, 1862 chrysippe Nixon, 1944 (Dacnusa), syn. n. of Chorebus brevicornis (Thomson, 1895) cortipalpis Nixon, 1937 (Dacnusa), syn. n. of Chorebus glabriculus (Thomson, 1895) ea Nixon, 1944 (Dacnusa), syn. n. of Chorebus brevicornis (Thomson, 1895) elegantula Nixon, 1937 (Dacnusa), syn. n. of Chorebus crenulatus (Thomson, 1895) mamertes Nixon, 1943 (Dacnusa), syn. n. of Exotela interstitialis (Thomson, 1895) melanocera Thomson sensu Nixon, 1937 (Dacnusa), syn. n. of Exotela flavicoxa (Thomson, 1895) monticola (Förster, 1862) (Dacnusa), comb. n. hitherto Brachystropha monticola 4-dentata Thomson, 1895 (Dacnusa (Dacnusa)), syn. n. of Amyras clandestina (Haliday, 1839) castaneiventris Thomson, 1895 (Dacnusa (Dacnusa)), syn. n. of Chorebus cinctus (Haliday, 1839 coracina Stelfox, 1954 (Dacnusa (Rhizarcha?)), syn. n. of Brachystropha monticola (Förster, 1862) flavicoxa (Thomson, 1895) (Exotela), comb. n. hitherto Dacnusa (Dacnusa) flavicoxa gilvipes (Haliday, 1839) (Exotela), comb. n. hitherto Alysia (Dacnusa) gilvipes interstitialis (Thomson, 1895) (Exotela), comb. n. hitherto Dacnusa (Dacnusa) interstitialis melanocera (Thomson, 1895) (Exotela), comb. n. hitherto Dacnusa (Dacnusa) melanocera oligomera Förster, 1862 (Isomerista), syn. n. of Coloneura stylata Förster, 1862 taras Nixon, 1943 (Merites), syn. n. of Coloneura stylata Förster, 1862 atae (Nixon, 1943) (Priaspis), comb. n. hitherto Chorebus atae aridula (Thomson, 1895) (Protodacnusa), comb. n. hitherto Dacnusa (Dacnusa) aridula litoralis Griffiths, 1964 (Protodacnusa), spec. n. ruthei Griffiths, 1964 (Protodacnusa), spec. n. tristis (Nees, 1834) (Protodacnusa), comb. n. hitherto Alysia tristis mutia Nixon, 1948 (Rhizarcha), syn. n. of Brachystropha monticola (Förster, 1862) nigricornis Förster, 1862 (Stiphrocera), syn. n. of Alysia ampliator (Nees, 1834) agnata Förster, 1862 (Synelix), syn. n. of Synelix semirugosa (Haliday, 1839) semirugosa (Haliday, 1839) (Synelix), comb. n. hitherto Alysia (Dacnusa) semirugosa exilis Förster, 1862 (Trisisa), syn. n. of Coloneura stylata Förster, 1862